Eksistensi Ilmu Falak di Pondok Pesantren Syekh Ahmad Daud An-Naqsyabandy - Padlan Padil (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2022)
Astronomy in Islamic Civilization is one of the sciences whose development has a significant influence on world civilization. Although this knowledge was discovered before Islamic Civilization, its continued existence is one of the manifestations and responses to the idea of pre-Islamic development of Astronomy This is in line with the scientific principle of Islamic civilization, which does not eliminate the process of previous civilizations, historically and intellectual property, which is incorporated as part of an extraordinary scientific process. In addition, the special position of this science can be found in the civilization of the archipelago, particularly in Indonesia, and one of its developments can be found in the Islamic Boarding School of Sheikh Ahmad Daud An-Naqsyabandy, located in Gunung Tua Julu Village, Batang Onang District, North Padang Lawas Regency. The results of this study contain the development of astronomy in general and specifically in the Islamic boarding school of Sheikh Ahmad Daud An-Naqsyabandy ,which played important role in the development of Islam in Gunung Tua Village, North Padang Lawas. This journal is the result of initial research that was developed through a scientific study of the role of the Sheikh Ahmad Daud Islamic Boarding School. The results obtained from this development research are the following: 1) the development of astronomy to the archipelago in general 2) the existence of astronomy in the learning process that takes place at the Islamic Boarding School of Sheikh Ahmad Daud An-Naqsyabandy 3) the application of astronomy to determine the prayer schedule 4) and the determination of the beginning of Ramadan fasting, which is still ongoing. The development of astronomy, which exists to this day in North Padang Lawas Regency, cannot be separated from the influence of the Islamic boarding school of Sheikh Ahmad Daud An-Naqsyabandy which is the only institution that teaches astronomy.